الزواج العرفي وإشكالاته في القانون الجزائري - نوال شنيني - فريد زرقون (المسيلة, 2023)
هدفت الدراسة إلى معرفة ماهية الزواج العرفي وأركانه وشروطه والصور المشابهة له وأسبابه وطرق كتابته من الجانب الفقهي وقانون الأسرة الجزائري وكذا طرق اثبات العقد العرفي وتسجيله في سجلات الحالة المدنية قانونا إذا كان متنازعا فيه أو لا. وكذا الآثار المترتبة عن الزواج العرفي على الأسرة كالآثار القانونية والمادية والاجتماعية. الكلمات المفتاحية:الزواج العرفي، إشكالات، آثار، الأسرة. Abstract: The study aimed to find out what customary marriage is, its pillars, conditions, similar images, reasons, methods of writing it from the jurisprudential side and the Algerian family law, as well as ways to prove the customary contract and register it in the civil status records legally if it is disputed or not. As well as the effects of customary marriage on the family, such as legal, material and social implications. Keywords: customary marriage, problems, effects, family.
Keywords: :الزواج العرفي، إشكالات، آثار، الأسرة.